Ex vivo evaluation of mucosal responses to vaccination with ALVAC and AIDSVAX of non-human primates - Herrera,C; Veazey,R; Lemke,MM; Arnold,K; Kim,JH; Shattock,RJ (Vaccines, 2022)
Non-human primates (NHPs) remain the most relevant challenge model for the evaluation of HIV vaccine candidates; however, discrepancies with clinical trial results have emphasized the need to further refine the NHP model. Furthermore, classical evaluation of vaccine candidates is based on endpoints measured systemically. We assessed the mucosal responses elicited upon vaccination with ALVAC and AIDSVAX using ex vivo Rhesus macaque mucosal tissue explant models. Following booster immunization with ALVAC/AIDSVAX, anti-gp120 HIV-1CM244-specific IgG and IgA were detected in culture supernatant cervicovaginal and colorectal tissue explants, as well as systemically. Despite protection from ex vivo viral challenge, no neutralization was observed with tissue explant culture supernatants. Priming with ALVAC induced distinct cytokine profiles in cervical and rectal tissue. However, ALVAC/AIDSVAX boosts resulted in similar modulations in both mucosal tissues with a statistically significant decrease in cytokines linked to inflammatory responses and lymphocyte differentiation. With ALVAC/AIDSVAX boosts, significant correlations were observed between cytokine levels and specific IgA in cervical explants and specific IgG and IgA in rectal tissue. The cytokine secretome revealed differences between vaccination with ALVAC and ALVAC/AIDSVAX not previously observed in mucosal tissues and distinct from the systemic response, which could represent a biosignature of the vaccine combination.